EMI and Beyond Internationalising Higher Education Curricula in Italy - Bagni, Marco (bu,press, 2021)
This collection presents the state of the art on English-medium instruction (EMI) / Integrating content and language (ICL) in Italian higher education, drawing attention to different critical aspects of the teaching/learning experience and highlighting the perspectives of various educational stakeholders regarding the effectiveness of tertiary study in a foreign language. The chapters draw on a range of methodologies, from multimodal participant observation, to action research, to video-stimulated recall (VSR), to questionnaires and interviews, in examining language policies and practices across various educational settings. Overall, the volume suggests that internationalisation succeeds best when the form of lessons (language) and the content of lessons (disciplinary concepts) are constructively aligned in curriculum planning and delivery. This integration process requires the strategic support of educators to guarantee the quality of learning in multilingual education.;